2022
DOI: 10.3390/buildings12081175
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Performance Target and Fragility of Masonry Infilled RC Frames under In-Plane Loading

Abstract: Masonry infilled RC frames are one of the most common structural forms, the damage of which, in earthquake events, usually cause serious losses. The determination of the seismic performance target is the key foundation of performance-based seismic evaluation and design for masonry infilled RC frames. In this paper, an extensive database of experimental tests on infilled RC frames loaded in an in-plane direction is collated. According to the crack propagation and elastic-plastic characteristics of infilled RC f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Some codes apply and state the concept of determining different levels of performance [38][39][40]. In addition, previous studies state that the damage to panels for infilled frame structures is divided into 3 to 4 levels [26][27][28][40][41][42]. Based on the experimental result, some researchers propose different structural damage limits using IDR.…”
Section: Damage States Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some codes apply and state the concept of determining different levels of performance [38][39][40]. In addition, previous studies state that the damage to panels for infilled frame structures is divided into 3 to 4 levels [26][27][28][40][41][42]. Based on the experimental result, some researchers propose different structural damage limits using IDR.…”
Section: Damage States Definitionmentioning
confidence: 99%
“…Zhang [44] proposes that the IDR limit is related to the shape and characteristics of the infill wall damage and refers to the existing performance index. A study conducted by Chun Hui Liu [41] classified the damage states of the infilled frame by considering the description of the damage and mechanical properties of infill walls. This damage description is based on the degree of cracking, block and mortar damage, loads in a plane and displacement.…”
Section: Damage States Definitionmentioning
confidence: 99%
“…Karjinni (2019) developed capacity spectrum-based fragility curves and demonstrated that the RC frames with masonry in ll and appropriate con guration of shear walls have enhanced performance in the seismic event in all modes of various damage levels. C. Liu, et al (2022) estimated the seismic performance targets in terms of the inter-story drift ratio obtained from the extensive literature survey of experimental results. Then, they applied four limit states to assess the failure pattern of masonry in ll RC frame structures.…”
Section: Introductionmentioning
confidence: 99%